Analisis Implementasi Strategi Perencanaan Pajak Penghasilan Badan sebagai Upaya Penghematan Beban Pajak pada PT Anggada Indo Asia - Amelia Chantika Fati’ah; Syamsul Bahri Arifin (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the implementation of corporate income tax planning strategies at PT Anggada Indo Asia as an effort to reduce tax expenses. A descriptive qualitative method was used, employing interviews, observations, and documentation. The results show that the company has not yet fully implemented tax planning, as evidenced by fiscal corrections made to several expenses that do not comply with tax regulations. These non-deductible expenses need to be better managed to minimize tax liabilities. The recommended strategies include adherence to applicable tax regulations, completeness of supporting documents, and the reclassification of non-deductible expenses to optimize tax deductions. After the implementation of tax planning strategies, the company achieved a tax expense reduction of IDR 2,816,430, which represents a 2.4% efficiency from the total tax liability. This demonstrates that effective tax planning can significantly reduce the tax burden in a legal manner, without violating tax laws or regulations. Furthermore, the study highlights the importance of strategic tax planning for companies, as it not only ensures tax compliance but also enhances financial efficiency. The findings suggest that with a well-executed tax planning strategy, companies can optimize their tax obligations, reduce unnecessary costs, and achieve better financial performance. This study emphasizes the need for companies to adopt systematic tax planning to maintain compliance while taking advantage of tax-saving opportunities within the legal framework.